2015
DOI: 10.1016/j.virol.2015.03.048
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I and TLR3 are both required for maximum interferon induction by influenza virus in human lung alveolar epithelial cells

Abstract: Pattern recognition receptors, such as retinoic acid-inducible protein I (RIG-I), Toll-like receptors 3 and 7 (TLR3 and 7), and nucleotide-binding oligomerization domain containing protein 2 (NOD2), play important roles in the recognition of influenza A virus (IAV), but their role in interferon (IFN) induction is still unclear, particularly in human lung. We investigated IFN induction by IAV in the A549 cell line as well as in primary human alveolar epithelial cells (AEC). TLR3/7, NOD2, RIG-I, and IFN expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 38 publications
(41 reference statements)
5
75
0
Order By: Relevance
“…The LAIV carriage+ group showed an enrichment for genes in TLR3 signalling cascade, RIG-I/MDA5 mediated induction of IFN-alpha/beta pathways and IFN-gamma signalling, which is in agreements with the induction of antiviral responses following LAIV vaccination 35 . Moreover, TLR4 signalling was also enriched in this group.…”
Section: Resultssupporting
confidence: 60%
“…The LAIV carriage+ group showed an enrichment for genes in TLR3 signalling cascade, RIG-I/MDA5 mediated induction of IFN-alpha/beta pathways and IFN-gamma signalling, which is in agreements with the induction of antiviral responses following LAIV vaccination 35 . Moreover, TLR4 signalling was also enriched in this group.…”
Section: Resultssupporting
confidence: 60%
“…Unlike genome-wide association studies, however, our approach had limited the number of candidate genes/SNPs for study, and a more detailed analyses on haplotypes and population substructure are infeasible with this design. The SNPs' effects on protein function, and how this might impact on viral clearance and/ or signaling of proinflammatory responses at different disease stages, would require further elucidation (eg, serial viral load and cytokine/chemokine measurements) [14,15,16,18,19,20,28]. D222G, H275Y, and R292K mutations should have a minimal impact on results because of their reported rarity [25,28,29,31,35].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to mouse data showing type I and predominantly type III IFN responses [33], we found that human lung tissue significantly increased members of all IFN types with an emphasis on type II IFN-γ, which was more than 15 times greater. Interestingly, studies on A549 cells, primary human AECs or even human lung tissue found supporting results for type I and III IFN, but unfortunately neglected the measurement of IFN-γ after IAV infection [34][35][36]. Current understanding allocates the cellular source of type II IFN-γ to activated T-lymphocytes and natural killer cells rather than AECs, therefore assuming a role in adaptive immune activation instead of innate antiviral activity [37].…”
Section: Discussionmentioning
confidence: 99%